Prognosis Epilepsi - Harsono, Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Prognosis is defined as the chance of recovery from a certain condition. Strictly, in epilepsy this means the chance of terminal remission once a patient has established a pattern of recurrent epileptic seizures. Questions concerning duration of treatment and long-term prognosis in childhood epilepsy are often raised by parents whose children are starting therapy with antiepileptic drugs. Many studies have focused on those issues and have examined the risk factors for poor prognosis as well as the risk of recurrence of seizures. The wide variation found in the risk of recurrence among those who have had a first seizure seems to be explained by differences In study design or differences in the characteristics of the study groups. In addition, the study of the prognosis of epilepsy has been confounded because of the fact that epilepsy is an expression of so many different underlying etiologies and syndromes.Prognosis of epilepsy should be informed clearly to the patients and/or parents. The clear information will improve the patient compliance in taking medication for a long time.Key Words : prognosis of epilepsy - remission - antiepileptic drugs - risk factors - recurrent epileptic seizures